Audits of Quality ISO 9000:2000 - Garcia Pantigozo, Manuel (2000)
Any system to work it has to be audited, you have to compare it versus regulated records and procedures, system assurance and quality management ISO 9000:2000 has s respective standard ISO 10011 which is a guide to audit quality systems .